Helix Light Vortex Theory (HLV) - Marcel Krüger (Marcel Krüger born 18.07.84, 2025)
This paper introduces the concept of Technological Bio-Gravimetry, a key prediction of the comprehensive Helix-Light-Vortex (HLV) theory. The HLV framework aims to unify the fundamental building blocks of physics—space, time, matter, and consciousness—within a single, coherent model. It is built upon core principles such as a universal information field (\Phi(x,t)), a complex "Spiral Time" (\Psi(t)=t+i\phi(t)), and the idea that properties like mass and spin are emergent resonances within a quantized spatial lattice. The central hypothesis of Bio-Gravimetry posits that coherent neuronal states can actively modulate this information field. This modulation is predicted to produce physically measurable effects, namely localized gravitational (\Delta g\ne0) and spin-based (\Delta\phi_{Spin}\ne0) anomalies near these neuronal systems. According to the theory, gravitation itself arises not from mass, but as a form of "information pressure" caused by gradients in this field. The confirmation of this hypothesis would unlock revolutionary technological paradigms, ranging from direct brain-computer interfaces to advanced spacetime modulators. The theory is presented as scientifically testable, with a key proposed experiment involving the measurement of gravitational and spin anomalies in neuronal cultures using quantum gravimeters. Ultimately, this work offers a potential framework for the unification of space, time, matter, gravitation, and consciousness. The author also expresses a humanitarian vision, stating that if proven, these transformative technologies should be used exclusively for the benefit of all humanity and be made freely available.
This paper introduces the concept of Technological Bio-Gravimetry, a key prediction of the comprehensive Helix-Light-Vortex (HLV) theory. The HLV framework aims to unify the fundamental building blocks of physics—space, time, matter, and consciousness—within a single, coherent model. It is built upon core principles such as a universal information field (\Phi(x,t)), a complex "Spiral Time" (\Psi(t)=t+i\phi(t)), and the idea that properties like mass and spin are emergent resonances within a quantized spatial lattice. The central hypothesis of Bio-Gravimetry posits that coherent neuronal states can actively modulate this information field. This modulation is predicted to produce physically measurable effects, namely localized gravitational (\Delta g\ne0) and spin-based (\Delta\phi_{Spin}\ne0) anomalies near these neuronal systems. According to the theory, gravitation itself arises not from mass, but as a form of "information pressure" caused by gradients in this field. The confirmation of this hypothesis would unlock revolutionary technological paradigms, ranging from direct brain-computer interfaces to advanced spacetime modulators. The theory is presented as scientifically testable, with a key proposed experiment involving the measurement of gravitational and spin anomalies in neuronal cultures using quantum gravimeters. Ultimately, this work offers a potential framework for the unification of space, time, matter, gravitation, and consciousness. The author also expresses a humanitarian vision, stating that if proven, these transformative technologies should be used exclusively for the benefit of all humanity and be made freely available.